2022
DOI: 10.1155/2022/5042762
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Fibroblast Growth Factor 21 in Fibrotic Diseases

Abstract: Fibrosis is a common pathological outcome of chronic injuries, characterized by excessive deposition of extracellular matrix components in organs, as seen in most chronic inflammatory diseases. At present, there is an increasing tendency of the morbidity and mortality of diseases caused by fibrosis, but the treatment measures for fibrosis are still limited. Fibroblast growth factor 21 (FGF21) belongs to the FGF19 subfamily, which also has the name endocrine FGFs because of their endocrine manner. In recent yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 167 publications
0
3
0
Order By: Relevance
“…FGF21 is a member of the FGF19 subfamily; it is primarily secreted from the liver under physiological conditions and other tissues, including adipose tissue, skeletal muscle, heart and kidney. Several studies have shown that high-levels of serum FGF21 have association with the loss of bone mineral density in adults and postmenopausal women [ 15 ]. Similarly, our study populations of both the groups were identified with higher serum levels of FGF21 and a statistical significant difference (p = 0.041) was observed between Group I and Group II.…”
Section: Resultsmentioning
confidence: 99%
“…FGF21 is a member of the FGF19 subfamily; it is primarily secreted from the liver under physiological conditions and other tissues, including adipose tissue, skeletal muscle, heart and kidney. Several studies have shown that high-levels of serum FGF21 have association with the loss of bone mineral density in adults and postmenopausal women [ 15 ]. Similarly, our study populations of both the groups were identified with higher serum levels of FGF21 and a statistical significant difference (p = 0.041) was observed between Group I and Group II.…”
Section: Resultsmentioning
confidence: 99%
“…BAT has less oil content, which is beneficial for reducing the inflammatory response after transplantation. A variety of batokines from BAT have been shown to have strong anti‐fibrotic effects, such as fibroblast growth factor 21 (FGF21), 23 β‐hydroxybutyric acid, 16 and the cold‐inducible complex general transcription factor II‐I repeat domain‐containing protein 1 14 . Therefore, BAT grafting alone may be superior to WAT in treating LoS.…”
Section: Discussionmentioning
confidence: 99%
“…74 As an anti-inflammatory cytokine, elevated FGF-21 may be considered as a compensatory response in early stage of metabolic disease. 75 It is worth noting that Firmicutes bacterium CAG:176, Firmicutes bacterium CAG:176_59_8, and Clostridium species CAG:678 were positively related to some glycerophospholipids and β-glucuronidase, while negatively related to triacylglycerols, imidazolepropionic acid, and FGF-21, suggesting that their depletion during menopause may adversely impact host metabolism. Furthermore, we demonstrated that depletion of F. prausnitzii and A. elongatum may partially mediate the relationship between menopause and depletion of certain phosphatidylcholine plasmalogens, providing a new potential mechanism for menopause-related lipidomic changes.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-21 is also regarded as an independent predictor of severe fatty liver in people with HIV 74 . As an anti-inflammatory cytokine, elevated FGF-21 may be considered as a compensatory response in early stage of metabolic disease 75 . It is worth noting that Firmicutes bacterium CAG:176 , Firmicutes bacterium CAG:176_59_8 , and Clostridium species CAG:678 were positively related to some glycerophospholipids and β-glucuronidase, while negatively related to triacylglycerols, imidazolepropionic acid, and FGF-21, suggesting that their depletion during menopause may adversely impact host metabolism.…”
Section: Discussionmentioning
confidence: 99%